FBXL16 Promotes Endometrial Progesterone Resistance via PP2AB55α/Cyclin D1 Axis in Ishikawa - Haoen Liu; Li Han; Liyan Zhong; Xiaodan Zhuang; Yan Peng (Journal of Immunology Research)
Background. F-box proteins are essential components of the E3 ubiquitin ligases which are involved in the regulation of almost all life activities such as cell cycle, proliferation, and apoptosis, which have become an important research and drug target. However, there are few studies on F-box and leucine-rich repeat protein 16 (FBXL16) in endometrial carcinoma. Methods. Clinical samples were collected for determining the correlation between FBXL16 and endometrial carcinoma. Cells were screened and established with Ishikawa cells which proved the fundamental role of FBXL16 in regulating cell proliferation and cell cycle. The MPA-resistant endometrial carcinoma cell line Ishikawa/MPA was established. FBXL16, PP2AB55α, and cyclin D1 were analyzed separately in MPA sensitive and resistant Ishikawa cells in vitro and in vivo. Results. The high expression of FBXL16 was positively correlated with MPA resistance and poor prognosis of endometrial cancer. MPA tolerance of endometrial cancer cells was inhibited by knockdown of FBXL16 in DNA content assessment, CCK-8, and colony formation. It was confirmed that FBXL16 inhibited the activity of substrate PP2AB55α by binding to PP2A, reduced the phosphorylation level at Thr308 site of AKT1, inhibited the expression of GSK-3β, and thus led to a significant decrease in the phosphorylation level of cyclin D1, which prevented the ubiquitination recognition and degradation of cyclin D1. Conclusion. In our experiments, FBXL16 binds PP2A to promote the dephosphorylation of Thr286 site of cyclin D1 via AKT1/GSK3β/cyclin D1 pathway, which is required for resisting the ubiquitination degradation and enhances the MPA resistance of Ishikawa.